ESTABLISHING CONSUMER SECURITY WITHIN THE PEER-TO-PEER LENDING ECOSYSTEM IN INDONESIA: A JURIDICAL ANALYSIS - Samuel, Yoel; Gunadi, Ariawan (Awang Long Law Review, 2025)
The development of financial technology has driven the rise of peer-to-peer lending services in Indonesia, enabling fast and accessible financing. However, this convenience is accompanied by increasing violations of consumer rights, including excessive interest rates, misuse of personal data, and standard agreements that disadvantage consumers. Many users fail to understand the legal implications of the terms they accept, reinforcing an imbalance of power between providers and consumers. Aggressive and unethical debt collection practices have also emerged due to weak regulatory oversight. This study aims to analyze the effectiveness of legal consumer protection within Indonesia’s peer-to-peer lending ecosystem. The research applies a normative juridical method through literature review, analysis of Supreme Court Decision No. 1206 K/Pdt/2024, and conceptual legal interpretation. Findings indicate that existing regulations, such as the Consumer Protection Act and the Financial Sector Development and Strengthening Act, have not been optimally enforced, particularly concerning standard clauses and data protection. The government must enhance public legal literacy and strengthen regulatory oversight and sanctions against violations. In conclusion, structural and substantive reforms of fintech regulations are needed to ensure that digital financial innovation advances in alignment with consumer justice and legal protection.